Phenotypic Characteristics Of Indigenous Sheep Of Bangladesh - Pervage, S; Ershaduzzaman, M; Talukder, MAI; Hasan, MN; Khandoker, MAMY (Bangladesh Journal of Animal Science, 2012)
This experiment was undertaken to know the phenotypic characteristics of native sheep. The study was conducted to investigate morphometric characters of sheep in three different field sites (Naogaon, Noakhali and Tangail) and Bangladesh Livestock Research Institute (BLRI) nucleus flock through close observation, measuring and record keeping. Characteristics of body weight, body length, heart girth, wither height, fore leg length, hind leg length, head length, ear length, ear width, horn length etc were collected from mature sheep. The results indicate that the average litter size, birth weight, weaning weight and body weight gain were comparatively higher in sheep of BLRI nucleus flock than those of other three regions. The average numbers of service/conception, post partum heat period (days), age at first heat (days), age at first lambing (days), lambing interval (days) were 1.30, 34.13, 266.50, 432.72, 192.17 respectively in BLRI nucleus flock which were comparatively better than the other three regions. The average litter size, birth weight (kg), weaning weight (kg) and body weight gain (g) in nucleus flock were 1.80, 1.19, 6.74 and 60.70 consequently. The overall performance of the sheep of BLRI nucleus flock were comparatively better than the others which may be due to the result of selective breeding, improve feeding, housing, health management etc. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9906 BJAS 2009; 38(1-2): 1-6